Data from: Evaluating tooth strontium and barium as indicators of weaning age in Pacific walruses - Clark, Casey; Horstmann, Lara; Misarti, Nicole (Zenodo, 2020)
A dataset of calcium-normalized 88 Sr and 137 Ba concentrations from laser ablation transects across the cementum layer of 107 (female: n = 84, male: n = 23) Pacific walrus (Odobenus rosmarus divergens) teeth. Dataset includes spreadsheets containing elapsed time of laser ablation transect in seconds (ElapsedTime_s; laser transect speed = 5μm/s), calcium-normalized strontium concentrations (Sr_ppm_m88; values below limit of detection replaced with 1/2*limit of detection, see methods), and calcium-normalized barium concentrations (Ba_ppm_m137; values below limit of detection replaced with 0.5*limit of detection). Photos (in .tif format) of tooth cementum used to estimate the positions of cementum growth layer groups are included for each animal. For teeth where more than one laser ablation scar is visible in the photo, an arrow is included to indicate the laser ablation scar that corresponds with the included trace element data. Finally, a Word document containing metadata (Catalog Number/ID, Sex, Median Age Est., Coll. Year, Est. Birth Year), weaning age estimates produced by both a visual and mathematical method (Sr Vis. Est., Sr Math. Est., Ba Vis. Est., Ba Math. Est.), and a descriptive grouping of the patterns of accumulation of Sr and Ba (Sr Pat., Ba Pat.) are included. See methods and accompanying paper in Methods in Ecology and Evolution for more details. Funding provided by: National Science Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100000001 Award Number: 1263848 Funding provided by: Bureau of Ocean Energy Management Crossref Funder Registry ID: http://dx.doi.org/10.13039/100012475 Award Number: Funding provided by: Coastal Marine Institute* Crossref Funder Registry ID: Award Number: Funding provided by: North Pacific Research Board Crossref Funder Registry ID: http://dx.doi.org/10.13039/100012635 Award Number: Funding provided by: Cooperative Institute for Alaska Research* Crossref Funder Registry ID: Award Number: Funding provided by: National Institutes of Health Crossref ...